2011
DOI: 10.1016/j.fluid.2011.02.001
|View full text |Cite
|
Sign up to set email alerts
|

On the behaviour of solutions of xenon in liquid cycloalkanes: Solubility of xenon in cyclopentane

Abstract: a b s t r a c tThe solubility of xenon in liquid cyclopentane has been studied experimentally and theoretically. Measurements of the solubility of xenon in liquid cyclopentane are reported as a function of temperature from 254.60 K to 313.66 K. The imprecision of the experimental data is less than 0.3%. The thermodynamic functions of solvation of xenon in cyclopentane, such as the standard Gibbs energy, enthalpy, entropy and heat capacity of solvation, have been calculated from the temperature dependence of He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…As previously explained, we have recently measured interaction enthalpies of dilute solutions of xenon in liquid n -alkanes and concluded that the interaction between xenon and the CH 3 group is stronger than that with CH 2 . , This information is taken into account by the TraPPE-UA model used in this work; it uses a larger nonbonded energy parameter for CH 3 than for CH 2 . This procedure, however, might seem to be in conflict with the simulation results because we have found that the excess enthalpy becomes more negative as the proportion of CH 2 group within the alkane molecule increases.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…As previously explained, we have recently measured interaction enthalpies of dilute solutions of xenon in liquid n -alkanes and concluded that the interaction between xenon and the CH 3 group is stronger than that with CH 2 . , This information is taken into account by the TraPPE-UA model used in this work; it uses a larger nonbonded energy parameter for CH 3 than for CH 2 . This procedure, however, might seem to be in conflict with the simulation results because we have found that the excess enthalpy becomes more negative as the proportion of CH 2 group within the alkane molecule increases.…”
Section: Resultsmentioning
confidence: 67%
“…Interestingly, this reduced temperature is very close to that at which H m E ( x = 0.5) vanishes for binary mixtures of n -alkanes (0.57–0.59). In the second one, we have been able to decompose the interaction enthalpy into its (xenon + CH 2 ) and (xenon + CH 3 ) contributions, confirming that the Xe–CH 3 interaction is stronger than Xe–CH 2 .…”
Section: Introductionmentioning
confidence: 55%
“…The results obtained from the Monte Carlo simulations for Henry ´s constant as a function of temperature are presented in Tables 2 And 3 (for xenon in n-alkanes and cycloalkanes, respectively), and plotted in Fig. 1 (xenon in n-alkanes) and 2 (xenon in cycloalkanes), along with experimental results from Pollack et al [20,21] and Bonifácio et al [23,33].…”
Section: Resultsmentioning
confidence: 99%
“…In Fig. 7, the enthalpy of solvation of xenon in cyclopentane and cyclohexane from experimental results [21,33] are also included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation